Effect of Variety and Weed Management Practices on Yield and Yield Attributes of Wheat - Sultana, MR; Alim, MA; Hossain, MB; Karmaker, S; Islam, MS (Journal of Environmental Science and Natural Resources, 2013)
An experiment was conducted at Agronomy Field Laboratory of Rajshahi University to evaluate the effect of variety and weeding regime on yield and yield components of wheat. Four varieties viz. Prodip -V1, Gourab -V2, Shatabdi -V3, Bijoy -V4 and five weeding regime viz. a) No weeding -W0, b) Weed free -W1, c) One hand weeding at 20 DAS -W2, d) Two hand weeding (1st at 20 DAS and 2nd at 42 DAS) -W3 and e) Lintur 70 WG @ 250 g ha-1 -W4 were included as treatments in the experiment. The experiment was laid out in a Split-plot Design with three replications. The results revealed that Prodip produced the highest grain yield (5.33 t ha-1) followed by Gourab (4.85 t ha-1), while the lowest grain yield (3.98 t ha-1) was obtained from Shatabdi. The highest grain yield (5.09 t ha-1) was obtained in Weed free (W1) followed by W3 (Two hand weeding) (4.89 t ha-1) and the lowest grain yield (4.13 t ha-1) was obtained in no weeding treatment (W0). The highest grain yield (5.64 t ha-1) was obtained from the combination of Prodip and weed free treatment (V1W1) and the lowest (3.57 t ha-1) was obtained from the combination between Shatabdi and no weeding treatment (V4W0). DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14800 J. Environ. Sci. & Natural Resources, 5(2): 91-96 2012